Sperm Oxidative Stress Is Detrimental to Embryo Development: A Dose-Dependent Study Model and a New and More Sensitive Oxidative Status Evaluation - Letícia S. de Castro (Oxidative Medicine and Cellular Longevity, 2016)
Our study aimed to assess the impact of sperm oxidative stress on embryo development by means of a dose-dependent model. In experiment 1, straws from five bulls were subjected to incubation with increasing H2O2 doses (0, 12.5, 25, and 50 μM). Motility parameters were evaluated by Computed Assisted System Analysis (CASA). Experiment 2 was designed to study a high (50 μM) and low dose (12.5 μM) of H2O2 compared to a control (0 μM). Samples were incubated and further used for in vitro fertilization. Analyses of motility (CASA), oxidative status (CellROX green and 2’-7’ dichlorofluorescein diacetate), mitochondrial potential (JC-1), chromatin integrity (AO), and sperm capacitation status (chlortetracycline) were performed. Embryos were evaluated based on fast cleavage (30 h.p.i.), cleavage (D=3), development (D=5), and blastocyst rates (D=8). We observed a dose-dependent deleterious effect of H2O2 on motility and increase on the percentages of positive cells for CellROX green, capacitated sperm, and AO. A decrease on cleavage and blastocyst rates was observed as H2O2 increased. Also, we detected a blockage on embryo development. We concluded that sperm when exposed to oxidative environment presents impaired motility traits, prooxidative status, and premature capacitation; such alterations resulting in embryo development fail.